2020
DOI: 10.1093/aobpla/plaa044
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic and environmental factors on variations of seed heteromorphism in Suaeda aralocaspica

Abstract: Seed heteromorphism (SH) is an adaptive strategy towards adversity in many halophytes. However, the underlying mechanisms and ecological significance of SH have not been deeply explored. Using Suaeda aralocaspica, a typical C4 annual halophyte without Kranz anatomy, we studied seed morphology, differentiation of morphs and fruit-setting patterns, and correlated these traits with germination responses, seed characteristics and heteromorphic seed ratio. To elucidate the genetic basis of SH, we analyzed correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 71 publications
0
7
0
2
Order By: Relevance
“…A plasticidade fenotípica de algumas espécies heteromórficas, como as proporções e os números de morfologia de frutos e sementes, tem sido considerada um mecanismo da espécie para lidar com ambientes imprevisíveis (Cao, et al, 2020).…”
Section: Resultsunclassified
“…A plasticidade fenotípica de algumas espécies heteromórficas, como as proporções e os números de morfologia de frutos e sementes, tem sido considerada um mecanismo da espécie para lidar com ambientes imprevisíveis (Cao, et al, 2020).…”
Section: Resultsunclassified
“…Suaeda aralocaspica has developed various strategies to adapt to heterogeneous conditions at different developmental stages, e.g., seed heteromorphism in the germination stage, SC C 4 assimilation pathway in the adult stage, growth enhancement by salt in the whole life cycle, etc. (Voznesenskaya et al, 2001 ; Wang et al, 2008 ; Cao et al, 2015 , 2020 ). However, the specific mechanism for early seedling development in an extreme environment has not been well understood so far.…”
Section: Discussionmentioning
confidence: 99%
“…According to meteorological data from 2008 to 2012 of the natural habitat of S. aralocaspica , the average annual precipitation is about 165 mm but is usually much less during the first 4 months (Cao et al, 2020 ). The higher moisture of soil in spring along with a much higher evaporation rate promotes the seasonal accumulation of large amounts of salinity on soil surface, which creates a hostile environment for seedling growth (Ma et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of environmental conditions, genetic mutations, and soil nutrient variations across districts may contribute to the observed diversity in seed counts. It was previously reported that the environmental factors and genetic mutations act as a potential influencer on the seeding pattern of fruits (Cao et al 2020). Also, the variation in the soil nutrients in different districts of Assam may be a reason, which contributes to the differences in seeding patterns among the accessions in the current study (Gnan et al 2014).…”
Section: Discussionmentioning
confidence: 99%